Perancangan Antarmuka Aplikasi Monteer dengan Metode Design Thinking - Fellyca Effendi; Kevin Andreas; Calvin Bertnas Valentino; Daniel Johan; Jasen Jonathan; Laurentius Ricardo Wijaya; Muhammad Rizky Pribadi (Universitas Multi Data Palembang, 2022)
Abstract: Many people have troubles in fixing their vehicles, calling in mechanics, and maintaining their vehicles. To overcome those problems, We developed Monteer application which will provide features like call a mechanic, guide book, tow, and more. In designing Monteer application, requires a long thinking process. In addition, the error in using the application also happens. So therefore, in designing Monteer UI,